2009
DOI: 10.1387/ijdb.082801hk
|View full text |Cite
|
Sign up to set email alerts
|

Gonad-stimulating substance-like molecule from the radial nerve of the sea cucumber

Abstract: Gonad-stimulating substance-like molecule (GSSL) was isolated from the radial nerve of the sea cucumber, Apostichopus japonicus (Aj-GSSL), and its partial DNA and protein sequences were characterized. The smaller part of the molecule that also retains GSSL activity was estimated. Radial nerve extract (RNE) induced germinal vesicle breakdown (GVBD) at 3 mg/ml in 85% of immature ovarian oocytes. Similar intensity of GSSL activity to RNE was seen in a fraction that contained peptides between 3 kDa and 10 kDa (3-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 38 publications
3
29
0
Order By: Relevance
“…Katow et al [14] identified a gonad-stimulating substance-like peptide (GSSL) of around 4.6 kDa in the nerve tissue of A. japonicus that induced GVBD in vitro at a concentration of 30 lg/ml. The potential of GSSL to act as a spawning inducer was not examined in this study, but immunohistochemical observations suggested that holocrine secretion of GSSL-containing granules takes place into the body cavity.…”
Section: Discussionmentioning
confidence: 99%
“…Katow et al [14] identified a gonad-stimulating substance-like peptide (GSSL) of around 4.6 kDa in the nerve tissue of A. japonicus that induced GVBD in vitro at a concentration of 30 lg/ml. The potential of GSSL to act as a spawning inducer was not examined in this study, but immunohistochemical observations suggested that holocrine secretion of GSSL-containing granules takes place into the body cavity.…”
Section: Discussionmentioning
confidence: 99%
“…The L-Ab and N-Ab were raised in mice using a synthetic peptide, AEIDDLAGNIDY, which constitutes a part of the physiologically active GSSL of A. japonicus (GenBank: Nucleotide AB434762) (Katow et al, 2009).…”
Section: Anti-gssl Antibody Properties For the Gim-kitsmentioning
confidence: 99%
“…For immunoblotting analysis, protein aliquots were blotted to nitrocellulose membranes that were then incubated with alkaline phosphatase (AP)-tagged goat anti-mouse IgG Ab (Sigma-Aldrich, Inc., St. Louis, MO. USA), with the colour developed as described before (Katow et al, 2009).…”
Section: Anti-gssl Antibody Properties For the Gim-kitsmentioning
confidence: 99%
See 2 more Smart Citations